Estudo ecofisiológico de Schinus terebinthifolius Raddi (Aroeira Vermelha) - Siqueira, Maria Carolina Nunes (2005)
Schinus terebinthifolius(Raddi) is a widely distributed species, commonly called “pimenta-rosa”. The seed origin studies detects a genetic variability within the species, in this, within the same species, seeds originated from different locations are subjected to climatic ( and environmental) variations, that result in bring out certain aspects of its genetic composition, that means, that environment of a certain location can cause the development of specific characteristics, that will not manifest in a different location.Plants can react to environmental stress in different manners, and the toleranceto stress is variable among species and even in the same species depending on the habitat. This is the so-called phenotype plasticity. Studies which analyses forest species seedling responses to environmental stress are very important, since they allow theunderstanding of development process of these species under different abiotic conditions, which can influence the production and future generations.This work investigated S. terebintifoliusseed germinationfrom two different habitats:one from the “Restinga” (R) habitat and the other from wet forest (FP)under theseabiotic conditions: light, temperature, water stress and osmotic stress,and seedling developmentunder water stress. Seeds from both environments germinated under light and dark conditions. Seed water content from both populationswas about 21 and 25%, with no statistical difference between them. The FP populationhad higher germination percentage (69%), compared with R (41%), with a statistical difference between them. Under water and osmotic stress, the FPpopulationshowed a better germination compared to R. The results suggest that seed physiology is related to their original environment. Seeds are probably expressing genetic features in response to environment.Seedlings were grown from two different seed population. They were submitted to water stress for a 4 months period, and their development was recorded. The results showed that the stress affected seedling development, from the two populationsorigin. However, seedlings from FP populationshowed a higher development in relation to those from R, mainly in the most stressing treatments. These results suggests to a higher adaptation potential to seedlings from FP population